Mulheres do Círculo de Oração: poder simbólico da Assembleia de Deus - Alves, Mary Angela Brito (2024)
This research paper addresses the theme "The Women of the Prayer Circle: the symbolic power of the Assemblies of God," investigating the lack of visibility of women in the Assemblies of God and examining the symbolic power they wield within the religious community. The research aims to fill a gap in the academic literature on the impact and role of women in religion, especially considering that, historically, they have been marginalized from formal religious power positions, often being seen only as subordinates. The study comprises interviews, observations, and document analyses to explore the dynamics of the Prayer Circle. Based on theories of symbolic and political power, it seeks to understand how these women, although often not formally recognized, exercise significant influence in the church and community. The results demonstrate that despite formal limitations, such as the prohibition from holding pastoral or administrative roles, the women of the Prayer Circle play significant roles within the Assemblies of God. They do not merely provide spiritual and emotional support but also influence important decisions within the community, demonstrating resilience and articulative capacity. These women are recognized for their ability to maintain and propagate power within a predominantly male structure. The research concluded that the women of the Prayer Circle possess an "invisible power" that profoundly affects the religious and social dynamics of the community. Although not officially recognized, this power is indispensable for the church's maintenance and highlights the symbolic importance these women hold within the Assemblies of God. This study has relevant implications for the academic understanding of gender dynamics in religious contexts and challenges the norms that limit women's roles. It indeed enhances the importance of female contributions, potentially inspiring a rethinking of gender roles in churches, stimulating debates on gender equality and power in religious institutions.